2010
DOI: 10.2466/07.pr0.107.6.847-859
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Attitude as a Mediator of the Relationship between Psychological Restoration in Nature and Self-Reported Ecological Behavior

Abstract: Environmental attitude and ecological behavior were investigated in relation to the use of nature for psychological restoration. Specifically, with survey data from 468 German university students, the role of environmental attitude was investigated as a mediator of the restoration-behavior relationship. Assuming that positive experiences in nature can have a broad influence on environmental attitudes, the New Ecological Paradigm (NEP) scale, an attitudinal measure with broad scope, was adopted. Hierarchical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 26 publications
5
37
1
Order By: Relevance
“…These findings complement what Kaiser et al (2011) define as "self-interested" use of nature. Similar to previously reported results in adults (Byrka et al, 2010;Hartig et al, 2001;Hartig et al, 2007), children may want to protect those environments from which they obtain psychological benefits. Fascination seems to be the restorative quality with the strongest relationship with environmental attitudes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These findings complement what Kaiser et al (2011) define as "self-interested" use of nature. Similar to previously reported results in adults (Byrka et al, 2010;Hartig et al, 2001;Hartig et al, 2007), children may want to protect those environments from which they obtain psychological benefits. Fascination seems to be the restorative quality with the strongest relationship with environmental attitudes.…”
Section: Discussionsupporting
confidence: 77%
“…This relation was partially mediated by people's environmental concern. Byrka, Hartig, and Kaiser (2010) have highlighted that attitudes might play an important role in this relation. The link between perceived restoration and self-reported proenvironmental behavior has been previously addressed (Hartig et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Byrka, Harting, and Kaiser (2010) reported psychological restoration experiences in nature to be a significant antecedent to environmental attitudes and environmentally responsible behaviors. In our study, previous self-reported educational actions (e.g., subscribing to magazines about the environment) as forms of environmentally responsible behavior were utilized as an aftermath of environmental attitudes and motivations.…”
Section: Limitations and Future Research Suggestionsmentioning
confidence: 96%
“…However, the intersection of social justice with environmental issues in psychology has been less fully examined. If, as research has suggested, healthy environments help promote positive outcomes such as lowered aggression, increased self-discipline, improved perceptions of health status, and even lower levels of road [2,3,4,5,6,7,8,9,10] then it stands to reason that psychologists should address environmental initiatives in the context of social justice.…”
Section: Introductionmentioning
confidence: 99%